Inclusion of hemimegalencephaly into the phenotypic spectrum of NPRL3 pathogenic variants in familial focal epilepsy with variable foci. (21st May 2019) - Canavati, Christina; Klein, Karl Martin; Afawi, Zaid; Pendziwiat, Manuela; Abu Rayyan, Amal; Kamal, Lara; Zahdeh, Fouad; Qaysia, Ikram; Helbig, Ingo; Kanaan, Moien
Abstract: Despite tremendous progress through next generation sequencing technologies, familial focal epilepsies are insufficiently understood. We sought to identify the genetic basis in multiplex Palestinian families with familial focal epilepsy with variable foci (FFEVF). Family I with 10 affected individuals and Family II with five affected individuals underwent detailed phenotyping over three generations. The phenotypic spectrum of the two families varied from nonlesional focal epilepsy including nocturnal frontal lobe epilepsy to severe structural epilepsy due to hemimegalencephaly. Whole‐exome sequencing and single nucleotide polymorphism array analysis revealed pathogenic variants in NPRL3 in each family, a partial ~38‐kb deletion encompassing eight exons (exons 8‐15) and the 3′‐untranslated region of the NPRL3 gene in Family I, and a de novo nonsense variant c.1063C>T, p.Gln355* in Family II. Furthermore, we identified a truncating variant in the PDCD10 gene in addition to the NPRL3 variant in a patient with focal epilepsy from Family I. The individual also had developmental delay and multiple cerebral cavernomas, possibly demonstrating a digenic contribution to the individual's phenotype. Our results implicate the association of NPRL3 with hemimegalencephaly, expanding the phenotypic spectrum of NPRL3 in FFEVF and underlining that partial deletions are part of the genotypic spectrum of NPRL3 variants.